Socjoterapia w profilaktyce w pracy z młodzieżą - Herman, Tomasz (Wydawnictwo Naukowe UAM, 2014)
The purpose of this article is to bring the idea of sociotherapy as one of forms of prophylaxis. In the first part sociotherapy and prophylaxis will be discussed as the key concepts of this subject. They will be discussed in the context of the therapeutic impacts of prophylaxis. In the second part the author will try to show the dimension of prophylactic sociotherapy in work with young people.
Sociotherapy in Prophylaxis in Work with Youth
Keywords: sociotherapy; prophylaxis; youth